Tuesday

November 25, 2014

November 25, 2014

Posted by **katie** on Tuesday, September 18, 2012 at 3:16pm.

(y-(10/y))^2+6(y-(10/y))-27=0

- precal -
**Steve**, Tuesday, September 18, 2012 at 3:45pm(y-(10/y))^2+6(y-(10/y))-27=0

his is just like the other one: Let u=y-1/y and you have

u^2 + 6u -27 = 0

(u+9)(u-3) = 0

(y - 10/y + 9)(y - 10/y - 3) = 0

(y^2 + 9y - 10)(y^2 - 3y - 10) = 0

(y+10)(y-1)(y-5)(y+3) = 0

**Answer this Question**

**Related Questions**

PreCal - Solve for x. -3x^2+8=-4

precal - solve for x: (x^2-2x)^2 -11(x^2-2x)+24

PreCal - Solve The Inequality 0 < -9x/x-x^2

precal - solve by subsituting 5x+4y=7 x-3y=9

precal 2 - solve the equation 4cos^2x-1=0

precal - How do you solve: sin[arccos(-2/7)] ?

PreCal - Solve Using Log Properties: 1/4 = 8^3x+5

Precal - Solve the exponential equation algebraically 5^(-t/2) = 0.20

PreCal - I'm suppose to solve log(3)-27=x I get 3^x=-27 I can't go any father ...

precal 2 - use the law of cosines to solve the triangle a=55, c=72, b=25